АНАГРАММА В СТРУКТУРЕ «ДОПОТОПНОГО ЕВАНГЕЛИЯ» КОНСТАНТИНА КЕДРОВА (Philological Studies, 2019)
Article «Anagram in the structure of poem «До-потоп-Ноя Ев-АнгелИЕ» of Konstantin Kedrov is devoted to study the role of anagrams in creating the imagery of this work. Anagram – a particular case of inversion in the space of the text – the most important principle of generation and penetration into the essence of the world. This principle is the main for Konstantin Kedrov, ideologist school of metametaphora, which existed in the 1980s, later the founder of ДООС (Voluntary society for protection of dragonflies), which exists until now. Anagram – the ancient technique of forming words and, according to Kedrov, means of their «resurrection» in our days. Moreover, the poet is trying to get back to the primitive, «anagram thinking» and promoting the creating of mythological picture of the world. In the poem Kedrov wanted to the names of Egyptian gods (Osiris, Seth, Isis etc.) gradually transformed in the name of Christ. Christ appearing in the history of forever repeating the day of creation and death as a future in the past, as the sun among the Gentiles, «inverse» the God of time Chronos. Time goes on and flowing backwards, so the «Sons die in the fathers».
Keywords: Anagram, inversion, metametaphora, Egyptian gods, Christ, time